Recepcja twórczości Wisławy Szymborskiej na Litwie - Dalecka, Teresa (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
Reception of works of Wisława Szymborska in Lithuania should be treated as a separate phenomenon. The translators of the poems of the Nobel Prize-winning Polish poetess are mainly Lithuania’s most prominent poets and translators. In addition to poems, there also appeared translation of the book review column entitled Lektury nadobowiązkowe (“Non-compulsory reading”). Nobelist’s poems are published in the literary and cultural magazines “Literatūra ir menas” (“Literature and Art”) and “Šiaurės Atenai” (“Northern Athens”). Her poems are often published in the original language as well as translation. However, there is no serious academic discourse on translated Szymborska’s literary works in Lithuania.